Evidence of Respiratory Syncytial Virus Spread by Aerosol. Time to Revisit Infection Control Strategies? - Kulkarni, Hemant; Smith, Claire Mary; Lee, Dani Do Hyang; Hirst, Robert Anthony; Easton, Andrew J.; O’Callaghan, Chris (American journal of respiratory and critical care medicine, 2016)
Respiratory syncytial virus (RSV) is a highly contagious pathogen with a huge global health impact. It is a major cause of hospital-acquired infection; a large number of those exposed develop infection. Those infected in hospital are at increased risk of a severe clinical course. Prevention of nosocomial spread currently focuses on spread by hand and large droplets. There is little research evidence to determine if aerosol spread of infectious RSV is possible. To determine if the air surrounding infants with RSV-positive bronchiolitis contains RSV in aerosolized particles that remain capable of causing infection. The amount of RSV contained in aerosolized particles produced by infants with bronchiolitis due to RSV was measured using viable impactor sampling. The ability of RSV contained in these particles to infect healthy and chronic obstructive pulmonary disease (COPD) human ciliated respiratory epithelium was determined. We showed for the first time that infants with RSV-positive bronchiolitis nursed in a ward setting or ventilated in intensive care produced large numbers of aerosol particles containing RSV that remained infectious and were capable of infecting healthy and COPD human ciliated epithelium. A significant amount of RSV was found in particles with aerodynamic diameters less than 5 μm. Many of the aerosolized particles that contained RSV in the air surrounding infants with bronchiolitis were sufficiently small to remain airborne for a significant length of time and small enough to be inhaled and deposited throughout the respiratory tract. It is likely that this leads to spread of infection to others, with dissemination of infection throughout the respiratory tract.